## Answer :

1.

**Substitution:**Start by substituting [tex]\( x = -1 \)[/tex] into the function [tex]\( f(x) \)[/tex]:

[tex]\[ f(-1) = 3(-1)^2 - 2(-1) - 7 \][/tex]

2.

**Evaluate [tex]\( (-1)^2 \)[/tex]:**Calculate the square of [tex]\(-1\)[/tex]:

[tex]\[ (-1)^2 = 1 \][/tex]

3.

**Multiply by 3:**Multiply 3 by the result of [tex]\((-1)^2\)[/tex]:

[tex]\[ 3 \times 1 = 3 \][/tex]

4.

**Evaluate [tex]\(- 2(-1)\)[/tex]:**Calculate [tex]\( -2 \times (-1) \)[/tex]:

[tex]\[ -2 \times (-1) = 2 \][/tex]

5.

**Combine the terms:**Now, add all the terms together:

[tex]\[ 3 + 2 - 7 \][/tex]

6.

**Simplify:**Perform the arithmetic operation:

[tex]\[ 3 + 2 = 5 \][/tex]

[tex]\[ 5 - 7 = -2 \][/tex]

Therefore, the value of [tex]\( f(-1) \)[/tex] is:

[tex]\[ f(-1) = -2 \][/tex]